STATE OF AGRO-FOOD FOREIGN TRADE IN BOSNIA AND HERZEGOVINA - Milovanović, Mirjana; Radosavac, Adriana; Knežević, Desimir (Economics of Agriculture, 2018)
Trade of agricultural products plays an important role in food security, development of production and processing of products, strengthening the economy and GDP growth. The aim of this paper is to establish the trend of trade of food, live animals, drinks and tobacco in Bosnia and Herzegovina (B&H). Foreign trade of food products in B&H has been investigated for the past six years (2012- 2017). In B&H, annual import of agricultural and food products exceeds BAM 2.5 million and the export is approximately BAM 600 million. Food production is a strategic interest of every country. The coverage of import by export was the highest in 2017 (29.9%) and 2016 (29.4%), while the lowest was in 2014 (18.4%). During the investigated period, there was a deficit of trade in B&H. Both export and import in agro-food sector have been increasing recently, while the volume of export has a higher growth than import.